Applied Strategies for Implementing Bilingual Programs in Madrasahs to Building Public Confidence - M Faiz; Hairun Nisak; Latifatus Saleha (Al-Qalam Institute, 2024)
The purpose of this research is to analyze the management strategies used by Islamic Boarding School in implementing bilingualism within and beyond classroom settings, as well as to evaluate the effectiveness of bilingual learning activities in achieving linguistic and educational goals. In an increasingly interconnected and globalized world, mastery of foreign languages such as English, Arabic, and others is a valuable skill. Bilingual learning programs in madrasas play a significant role in fostering such skills, equipping students with enhanced academic, professional, and personal opportunities. This study employs a qualitative approach using an ethnographic research design. Data collection methods include direct field observations, in-depth interviews with key stakeholders, and analysis of relevant documents. The data analysis process involves reduction, presentation, validation, and conclusion drawing to ensure the validity and reliability of the findings. The research reveals that bilingual learning at Islamic Boarding School is implemented through a well-conceptualized strategy aimed at achieving specific language standards. The school integrates bilingual education both inside and outside the classroom, fostering an immersive learning environment that supports language acquisition. This research is expected to contribute to the understanding of effective bilingual education management in Islamic boarding schools.